1984
DOI: 10.1152/jappl.1984.56.3.810
|View full text |Cite
|
Sign up to set email alerts
|

A model of embolic chronic pulmonary hypertension in the dog

Abstract: Despite numerous efforts, a reliable model of chronic embolic pulmonary hypertension has not been established. To develop such a model five conscious mongrel dogs were embolized repeatedly over 16-30 wk with Sephadex microspheres 286 +/- 70 micron in diameter. Hemodynamic and respiratory measurements were obtained just prior to each embolization. Chronic pulmonary hypertension developed in all dogs. Pulmonary hypertension was not accounted for by increased cardiac output, wedge pressure, right atrial pressure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Another documented animal model of PAH involves the formation of chronic emboli in pulmonary vessels. Shelub et al induced chronic embolic PAH through repeated microembolizations with the injection of Sephadex ® microspheres 20. The utilization of this approach allows different-sized vessels to be targeted depending on the diameter size of the microspheres that are injected, and vascular obstruction and vasoconstriction are the primary mechanisms of the high pulmonary vascular resistance that occurs 20,21.…”
Section: Animal Models Of Pulmonary Hypertensionmentioning
confidence: 99%
“…Another documented animal model of PAH involves the formation of chronic emboli in pulmonary vessels. Shelub et al induced chronic embolic PAH through repeated microembolizations with the injection of Sephadex ® microspheres 20. The utilization of this approach allows different-sized vessels to be targeted depending on the diameter size of the microspheres that are injected, and vascular obstruction and vasoconstriction are the primary mechanisms of the high pulmonary vascular resistance that occurs 20,21.…”
Section: Animal Models Of Pulmonary Hypertensionmentioning
confidence: 99%
“…A titratable infusion rate plus the long duration of insult enabled us to minimize animal death by preventing fatal events such as acute lung edema or acute heart failure that have been reported in previous studies [10,12]. Also, PaO 2 levels were maintained above 80 mmHg or higher through the experimental course.…”
Section: Discussionmentioning
confidence: 99%
“…Shelub et al [10], Weimann et al [12], and Sato et al [21] reported that recurrent microembolism with microspheres caused pulmonary hypertension. Unfortunately, a high mortality rate or a lack of histologic evidence of pulmonary vascular remodeling weakens the interpretation of these studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations